Determinación de zonas susceptibles a erosión hídrica en los cantones de Catamayo y Gonzanamá de la provincia de Loja, utilizando sistemas de información geográfica (SIG) y teledetección - Vega Loján, Julio Leonardo (2016)
Water erosion is a process of land degradation caused mainly by the decrease of natural vegetation cover that is converted into other anthropogenic land cover types. The purpose of this research was to estimate the current and potencial water erosion with different scenarios of vegetation cover in Catamayo and Gonzanamá cantons of the province of Loja, using the RUSLE model (Revised Universal Soil Loss Equation) by Information Geographic Information Systems and remote sensing. Erosivity (factor R) was estimated by the Modified Fournier Index (MFI) based on the data of monthly precipitation over a period of 35 years. For erodibility (factor K), the depth, soil structure, permeability, organic matter, texture and very fine sand percentage was determined. The length of the slope and slope (LS factor) was generated by the Digital Elevation Model (MDT) based on SRTM. Vegetation Cover factor (C) was produced by digitalization of orthophotos at scale 1: 3.000. The factor management practices (P) was assigned a value of 1 because they were not identified in the working scale. The results are alarming because in the cantons studied the current erosion is from 39 126 to 54 695 t/ha/year, mainly because a large area of these cantons is used for agriculture and livestock. The advance of the agricultural frontier to establish perennial and annual crops or grazing is another important factor that destroys the natural vegetation cover with forest fires always linked. With a negative scenario that implies that there is not a damping effect of vegetative cover, erosion rates could increase by up to 86%, which the transcendental importance of this factor in the soil loss is evident. As a measure to reduce soil erosion in areas most susceptible, a cropping system based on the contours, terracing of slow formation and passive restoration of the bushes, which the category of high susceptibility to erosion will be reduced to 42%. These results should be considered by decision makers, with the aim of contribute to mitigating water erosion and soil degradation.